2021
DOI: 10.1002/anie.202015948
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Transfer to Enhance NOE Cross‐Peaks among Labile Protons: Applications to Imino–Imino Sequential Walks in SARS‐CoV‐2‐Derived RNAs

Abstract: 2D NOESY plays a central role in structural NMR spectroscopy. We have recently discussed methods that rely on solvent‐driven exchanges to enhance NOE correlations between exchangeable and non‐exchangeable protons in nucleic acids. Such methods, however, fail when trying to establish connectivities within pools of labile protons. This study introduces an alternative that also enhances NOEs between such labile sites, based on encoding a priori selected peaks by selective saturations. The resulting selective magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…[26] As 1 H assignments for this RNA fragment have been reported, [27] experiments were carried out mainly to examine the presence of artifacts and relative sensitivities. As already demonstrated in Ref [14] the most basic of these experiments, SMT, will significantly enhance cross-relaxation peaks when compared to its conventional counterpart; under the assayed conditions (grey vs black traces in Figure 4), ca. 4-and 6-fold SNR enhancements per unit time (SNRT) were observed for iminoimino and imino-amino proton correlations, respectively.…”
Section: Assessing Homonuclear Magnetization Transfers In Rna Fragmen...supporting
confidence: 52%
See 3 more Smart Citations
“…[26] As 1 H assignments for this RNA fragment have been reported, [27] experiments were carried out mainly to examine the presence of artifacts and relative sensitivities. As already demonstrated in Ref [14] the most basic of these experiments, SMT, will significantly enhance cross-relaxation peaks when compared to its conventional counterpart; under the assayed conditions (grey vs black traces in Figure 4), ca. 4-and 6-fold SNR enhancements per unit time (SNRT) were observed for iminoimino and imino-amino proton correlations, respectively.…”
Section: Assessing Homonuclear Magnetization Transfers In Rna Fragmen...supporting
confidence: 52%
“…This was illustrated in ref. [14], which showed that although HMT could provide reliable cross-peaks between different spin pools, it will in general fail when connectivities are sought within the same pool of spins -e. g., when seeking imino-imino correlations within nucleic acids. This problem originates from Hadamard assumption of a linear independence between the weightings imparted to the various peaks during its frequency encoding.…”
Section: Hmt and Noes: The Problem Of Intra-group Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 We then proceed by describing our predictions on four elements of increasing complexity ( Figure 1 ) and discuss the agreement with available NMR measurements. 32 , 33 Stem loop 5a (SL5a) is part of the four-way junction SL5 containing the AUG starting codon, whose function is linked to RNA packaging. 34 Stem loop 1 (SL1) has been suggested to play a role in escaping the viral mechanism inhibiting mRNA translation.…”
Section: Introductionmentioning
confidence: 99%